2020
DOI: 10.1186/s42077-020-00113-7
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone as a bupivacaine adjuvant for ultrasound-guided interscalene brachial plexus block: a prospective randomized study

Abstract: Background Finding adjuvants to local anesthetic used in interscalene block that could efficiently extend the analgesia duration has recently been the focus of researchers. The aim of the work was to determine whether the addition of perineural dexamethasone to bupivacaine in-ultrasound guided interscalene block would prolong the duration of sensory analgesia in patients undergoing shoulder surgery. Results This prospective, randomized, double-blinded study comprised 50 patients. They were randomly subdivided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…The results showed that the intensity of pain in the experimental group (dexamethasone) was lower than in the control group at 12 and 24 hours after surgery, indicating that dexamethasone was able to significantly reduce pain in patients. These findings are consistent with the results of studies by Pehora et al ( 7 ), Yayik et al ( 10 ), Badran et al ( 11 ), and Kim et al ( 12 ). For instance, Badran et al demonstrated that adding 8 mg of perineural dexamethasone to 30 cc of bupivacaine 0.5% improved postoperative pain relief in shoulder surgery without apparent side effects and prolonged the duration of the block ( 11 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the intensity of pain in the experimental group (dexamethasone) was lower than in the control group at 12 and 24 hours after surgery, indicating that dexamethasone was able to significantly reduce pain in patients. These findings are consistent with the results of studies by Pehora et al ( 7 ), Yayik et al ( 10 ), Badran et al ( 11 ), and Kim et al ( 12 ). For instance, Badran et al demonstrated that adding 8 mg of perineural dexamethasone to 30 cc of bupivacaine 0.5% improved postoperative pain relief in shoulder surgery without apparent side effects and prolonged the duration of the block ( 11 ).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with the results of studies by Pehora et al ( 7 ), Yayik et al ( 10 ), Badran et al ( 11 ), and Kim et al ( 12 ). For instance, Badran et al demonstrated that adding 8 mg of perineural dexamethasone to 30 cc of bupivacaine 0.5% improved postoperative pain relief in shoulder surgery without apparent side effects and prolonged the duration of the block ( 11 ). They also suggested using bupivacaine with dexamethasone instead of liposomal bupivacaine ( 12 ).…”
Section: Discussionsupporting
confidence: 93%
“…2 Understanding the pathophysiology of pain, surgical procedures type, and patient factors related to increased pain, such as anxiety and depression are important for adequate control of postoperative pain. 3 Optimal management of postoperative pain is an important part of care of surgical patient, and insufficient control of pain may lead to unwanted effects, 4 such as prolonged recovery, prolonged hospital stay, and chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…In 161 studies, patients received a supraclavicular brachial plexus block, 26,29–160 in 40 studies, patients received an axillary brachial plexus block, 24,27,161–198 in 28 studies, an interscalene block was performed, 25,199–220 in 11 studies, patients received an infraclavicular brachial plexus block, 221–231 one study used a coracoid approach to brachial plexus block 232 and one study used a suprascapular combined with axillary nerve block 233 . A detailed description of included studies is presented in the supplemental content (supplemental table 3, http://links.lww.com/EJA/A839).…”
Section: Resultsmentioning
confidence: 99%